Efficient and Fast Synthesis of Few‐Layer Black Phosphorus via Microwave‐Assisted Liquid‐Phase Exfoliation. Issue 12 (8th November 2017) - Bat‐Erdene, Munkhjargal; Batmunkh, Munkhbayar; Shearer, Cameron J.; Tawfik, Sherif Abdulkader; Ford, Michael J.; Yu, LePing; Sibley, Alexander J.; Slattery, Ashley D.; Quinton, Jamie S.; Gibson, Christopher T.; Shapter, Joseph G.
Abstract: High‐quality, few‐layer black‐phosphorus (BP) flakes are prepared in a common organic solvent with very short processing times using microwave‐assisted liquid‐phase exfoliation. A comprehensive range of analysis, combined with density‐functional theory calculations, confirms that the product prepared using the microwave technique is few‐layer BP with small‐ and large‐area flakes. The suspended exfoliated BP sheets show excellent stability, while samples dispersed onto silicon from the suspensions exhibit low oxidation levels after several days in ambient conditions. This straightforward synthesis method is facile, efficient, and extremely fast, and does not involve use of any surfactant or ultrasonication steps and will facilitate future development of phosphorene research. Abstract : Facile and fast production of high‐quality, few‐layer black‐phosophorus sheets via a microwave‐assisted liquid‐phase exfoliation method is demonstrated. This method does not involve the use of any surfactant or ultrasonication steps and will facilitate future development of phosphorene research.